Perancangan Dan Pengembangan Graphıc Desıgn Berupa E-Katalog Pada Royale Laundry - Jose Armando; Deli Deli (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Royale Laundry was established in 2015, the location of Royale Laundry is located in Komp. Nagoya point Blok H No 8, Batam. Royale Laundry is a shop engaged in laundry services. In the era of globalization and increasingly rapid technological advances encourage people to be more active in using the internet today, apart from sharing information, the internet is also used as a means of promoting a product or service so that it is easier for people to find the product or service they need and the owner of the product or service easier to market. its product or service. This activity aims to help Royale Laundry to the public to find out the services, laundry services at Royale Laundry and provide tangible results. Promoting Royale Laundry by creating a catalog, namely an E-catalog using Adobe Photoshop CC 2018 and publishing it on Instagram. Data collection methods used: observation and interviews, with the design process design, predesign, design, postdesign. Suggestions for Royale Laundry shop owners, are expected to be active in introduction and promotion using social media or the internet in various social media platforms.